Assessing socio-scientific reasoning through local water issues: instrument development for preservice elementary teachers - Puji Winarti; Sri Haryani; Sri Wardani; Langlang Handayani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The study aims to develop and validate a Socio-Scientific Reasoning (SSR) assessment instrument based on local water issues for preservice elementary teachers. The simplified Research and Development (R&D) method from the Borg & Gall model was used in this study. The development process includes three main stages: preliminary study, instrument development and Validation, and limited trials. The instrument was designed around six key dimensions of SSR and consists of 24 extended-response items, contextualized within a conflict over the distribution of Senjoyo springs in Semarang Regency. Content validation was done through expert review using Aiken's V, while empirical validity and reliability were tested using the Rasch model. The results showed that most questions were valid and reliable, with high internal consistency. The instrument trial with 108 preservice elementary school teachers showed that participants' SSR abilities varied, with the highest achievements in the inquiry and context-bound dimensions and the lowest in the skepticism and affordances of science and non-science considerations dimensions. This study emphasizes developing SSR instruments tailored to local contexts to support critical, reflective, and contextually grounded elementary science learning.